2021
DOI: 10.1371/journal.pone.0255632
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use on 74 Japanese pig farms in 2019: A comparison of Japanese and European defined daily doses in the field

Abstract: Defined daily doses (DDD) have been established in human medicine to standardize the measurement of treatment in a population. In veterinary medicine, the European Medicine Agency published defined daily dose (DDDvet) values for antimicrobial agents used in food-producing animals in 2016. National defined doses (DDDjp) for antimicrobials used for pigs in Japan have recently been determined. The aim of this study was to compare the results of calculated antimicrobial use in the field using the DDDjp and DDDvet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…(ii) Indigenous bacteria should have better resistance to stress, such as antibiotics and competition from other intestinal microbes. Antibiotics, such as penicillins, are widely used in the swine industry ( 50 , 51 ). We tested the sensitivity of Y18J to 26 antibiotics (Table S1) and found that it was resistant to penicillins, erythromycin, chloramphenicol, and norfloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Indigenous bacteria should have better resistance to stress, such as antibiotics and competition from other intestinal microbes. Antibiotics, such as penicillins, are widely used in the swine industry ( 50 , 51 ). We tested the sensitivity of Y18J to 26 antibiotics (Table S1) and found that it was resistant to penicillins, erythromycin, chloramphenicol, and norfloxacin.…”
Section: Discussionmentioning
confidence: 99%